A novel Multi-perspective benchmarking framework for selecting image dehazing intelligent algorithms based on BWM and group VIKOR techniques - Abdulkareem, Karrar Hameed (Tanjong Malim, 2020)
A novel Multi-perspective benchmarking framework for selecting image dehazing intelligent algorithms based on BWM and group VIKOR techniques by Abdulkareem, Karrar Hameed